Flexural behavior of rebar truss stiffened cold-formed U-shaped steel-concrete composite beams. (November 2018) - Liu, Jiepeng; Zhao, Yi; Chen, Yohchia Frank; Xu, Shaoqian; Yang, Yuanlong
Abstract: This paper presents a new configuration of rebar truss stiffened cold-formed U-shaped steel-concrete composite beams (RCUCB), of which the upper opening part of the steel U-section is connected by a rebar truss so that the torsional stability can be enhanced. A bending test was carried out on ten specimens considering the following three parameters: shear connection degree, tensile reinforcement ratio, and beam depth. The specimens exhibit three failure modes under certain conditions: longitudinal slip when tensile reinforcement is absent and the full shear connection cannot be attained; vertical uplift when the beam is furnished with detailed longitudinal tensile reinforcement or a full shear connection; both splitting and uplift when the beam is provided with a full shear connection. It is found that RCUCB possesses both high bending capacity and good ductility. Cracks and deformations are mainly controlled by the longitudinal reinforcement, while the ductility is improved by shear studs. The ductility factor can reach 17.6 by optimizing the configuration of longitudinal reinforcement and shear studs and the slip between the steel and the concrete can be reduced by 91% when the beam is installed with detailed longitudinal tensile reinforcement. Moreover, the ultimate bending capacity was calculated according to the EC4 and JGJ 138 codes with the consideration of the following three modification factors: λ b, λ h, and λ c to account for the effective width of the slab, the effective depth of steel web, and the actual concrete compressive strength, respectively. The calculated values agree well with the test results. Graphical abstract: Unlabelled Image Highlights: New cold-formed U-shaped steel-concrete composite beam (RCUCB) is studied experimentally. Longitudinal slip, vertical uplift, and splitting failures were observed in the experiment. Deformations of concrete are controlled mainly by longitudinal reinforcement and ductility is improved by shear studs. Furnishing with detailed longitudinal tensile reinforcement can significantly reduce the slip between steel and concrete. Bending capacity can be calculated according to the EC4 and JGJ 138 codes considering three modification factors.